The Use of Bokashi to Enhance Agricultural Productivity of Marginal Soils in Southeast Sulawesi, Indonesia. - Karimuna, La; Rahni, Nini Mila; Boer, Dirvamena (Department of Agronomy and Horticulture, IPB University, 2016)
The yield of agriculture crops tends to be decreasing in many parts of world including in Indonesian farmers’ land. One of the causes of the decreased yields is the reduction of organic matter in the soil. Peanut is one of the important crops in southeast Sulawesi and is usually intercropped with maize. However, the yield of peanut and maize crops were low as they were grown in marginal lands that have low nutrient contents, low CEC, high acidity, and low organic matter. The objectives of this paper were to summarize the results of our studies on the use of bio fertilizer bokashi plus fertilizer to improve peanut yields grown in marginal soil in southeast Sulawesi, Indonesia. The study also examined the agronomical performance of several local peanut varieties which had high adaptability to the local conditions and marginal lands. The results of this study demonstrated that application of mulch and bokashi increased maize and peanut production, seed dry weight and 100-seed weight. This practice has potentials to be applied in other agricultural lands of southeast Sulawesi region with similar soil and climatic condition to increase peanut yield, and promote the sustainable agriculture production of the region.